Mechanical and Physical Properties of Recycled Carton Sheets treated with Copolymer Latex BuA/MMA and BuA/St through Two Techniques - Amal H Abdel-kader (Institute of Advanced Engineering and Science, 2014)
The aim of this work is to get rid of agricultural, paper wastes which consider a big environmental problem and their utilization in the production of economic products of some special applications. The use of paper-pulp packaging has become more attractive than traditional materials. In our work the mechanical and physical properties of recycled carton treated with copolymer latex butyl acrylate – methylmethacrylate emulsified copolymer (BuA/MMA) were measured through two techniques. Dipping recycled carton in different concentrations of emulsified BuA - MMA (2-4 %) copolymer and using different concentration of BuA - MMA emulsified copolymer (1-10 %) added during sheets making. From the results, a slight increase in the breaking length, cobb by treated sheets with different concentrations of the copolymer. But the burst and tear factors were decreased through the dipping effect. The breaking length of sheets increased at 1% copolymer, and then deceased by increasing the copolymer concentration. Whereas tear, burst factors and cobb increased through the addition of copolymer during paper making. Thermal gravimetric analysis (TGA) of samples was measured. The Microstructure of untreated and treated recycled carton sheets were clarified using SEM.